Big Law in Latin America and Spain Globalization and Adjustments in the Provision of High-End Legal Services (Springer International Publishing, 2018)
This book, part of the Stanford Law School research project on the future of the legal profession, thoroughly examines the future of "big law," defined as the large and mid-size multiservice highly specialized law firms that provide sophisticated, complex and generally costly legal work to multinationals, large and mid-size domestic corporations, and other business clients. By systematically gathering, assessing, and analyzing the best available quantitative and qualitative data on the first tier of the corporate legal services market of Latin America and Spain, and interviewing a broadly representative sample of corporate legal officers, law firm partners, and other stakeholders in each of the countries covered, this book provides a nuanced perspective on changes in "big law" during the last two decades until the present. It also explores the factors that are driving these changes, and the implications for the future of legal profession, legal education and its relationship with the corporate sector and society in general.